Avian Pathogenic Escherichia coli (APEC) Strain-Dependent Immunomodulation of Respiratory Granulocytes and Mononuclear Phagocytes in CSF1R-Reporter Transgenic Chickens - Alber, Andreas; Morris, Katrina M.; Bryson, Karen J.; Sutton, Kate M.; Monson, Melissa S.; Chintoan-Uta, Cosmin; Borowska, Dominika; Lamont, Susan J.; Schouler, Catherine; Kaiser, Pete; Stevens, Mark P.; Vervelde, Lonneke (Frontiers in Immunology, 2020)
Avian pathogenic Escherichia coli (APEC) cause severe respiratory and systemic disease in chickens, commonly termed colibacillosis. Early immune responses after initial infection are highly important for the outcome of the infection. In this study, the early interactions between GFP-expressing APEC strains of serotypes O1:K1:H7 and O2:K1:H5 and phagocytic cells in the lung of CSF1R-reporter transgenic chickens were investigated. CSF1R-reporter transgenic chickens express fluorescent protein under the control of elements of the CSF1R promoter and enhancer, such that cells of the myeloid lineage can be visualised in situ and sorted. Chickens were separately inoculated with APEC strains expressing GFP and culled 6 hours post-infection. Flow cytometric analysis was performed to phenotype and sort the cells that harboured bacteria in the lung, and the response of the sorted cells was defined by transcriptomic analysis. Both APEC strains were mainly detected in CSF1R-transgene neg (CSF1R-tg neg) and CSF1R-tg low MHC II neg MRC1L-B neg cells and low numbers of APEC were detected in CSF1R-tg high MHC II pos MRC1L-B pos cells. Transcriptomic and flow cytometric analysis identified the APEC pos CSF1R-tg neg and CSF1R-tg low cells as heterophils and the APECpos CSF1R-tg high cells as macrophages and dendritic cells. Both APEC strains induced strong inflammatory responses, however in both CSF1R-tg neg/low and CSF1R-tg high cells, many immune related pathways were repressed to a greater extent or less activated in birds inoculated with APEC O2-GFP compared to APEC O1-GFP inoculated birds. Comparison of the immune pathways revealed the aryl hydrocarbon receptor (AhR) pathway, IL17 and STAT3 signalling, heterophil recruitment pathways and the acute phase response, are modulated particularly post-APEC O2-GFP inoculation. In contrast to in vivo data, APEC O2-GFP was more invasive in CSF1R-tg high cells in vitro than APEC O1-GFP and had higher survival rates for up to 6 hours post-infection. Our data indicate significant differences in the responses induced by APEC strains of prevalent serotypes, with important implications for the design and interpretation of future studies. Moreover, we show that bacterial invasion and survival in phagocyte populations in vitro is not predictive of events in the chicken lung.